Inhibitory Activity of Levofloxacin against MDR Staphylococcus aureus and Pseudomonas aeruginosa Clinical Isolates - Lisa Nathalie; Lindawati Alimsardjono; Isnaeni Isnaeni (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2019)
Introduction: Staphylococcus  aureus  and  Pseudomonas  aeruginosa  are the most dangerous  and important species among  their genus.  These  bacteria  are often  resistant  to  many  classes  of antimicrobial  agents;  which  make difficulties in selecting appropriate drug to treat infections. Multidrug-resistance occurs readily in hospitals for which antimicrobials  agents  were   used  widely. Objective: The  aims  of  this  study  was  to  determine  minimum  inhibitory concentration  (MIC) and  minimum bacterial  concentration  (MBC) of levofloxacin  against 22 multidrug  resistant- clinical (MDR) strains of Staphylococcus aureus and Pseudomonas aeruginosa isolated from patients pus and urine in hospital. Methods: Determination of the MIC was performed by macro-dilution broth assay as recommended by Clinical and Laboratory Standards Institute (CLSI), while the MBC was determined one-step further after the MIC determination. Results: It was found that MIC of the levofloxacin were (0.3 ± 0.0) - >0.5 µg/mL and (0.2 ± 0.1) - (1.0 ±0.0)µg/mL against S. aureus from pus and urine, respectively.  In addition, higher MICs were yielded against P. aeruginosa, (1.0 ± 0.0) - >8.0 µg/mL and (0.7 ± 0.3) - (3.0 ± 1.2) µg/mL for pus and urine isolates respectively. Similar to MICs, the MBCs against P. aeruginosa were higher than S. aureus, (0.6 ± 0.0) - > 4.0 µg/mL and (0.3 ± 0.0) - >8.0 µg/mL isolated from pus and urine respectively, (2.0 ± 0.6) - > 8.0 µg/mL and (3.0 ± 1.2) - >7.0 µg/mL against P. aeruginosa from pus and urine respectively. Conclusion: The levofloxacin was still susceptible as bacteriostatic against isolates from both body fluids, but not bactericidal towards all isolates.